Evidence for a Myotomal Hox/Myf Cascade Governing Nonautonomous Control of Rib Specification within Global Vertebral Domains - Vinagre, Tânia (2016)
Hox genes are essential for the patterning of the axial skeleton. Hox group 10 has been shown to specify the lumbar domain by setting a rib-inhibiting program in the presomitic mesoderm (PSM). We have now produced mice with ribs in every vertebra by ectopically expressing Hox group 6 in the PSM, indicating that Hox genes are also able to specify the thoracic domain. We show that the information provided by Hox genes to specify rib-containing and rib-less areas is first interpreted in the myotome through the regional-specific control of Myf5 and Myf6 expression. This information is then transmitted to the sclerotome by a system that includes FGF and PDGF signaling to produce vertebrae with or without ribs at different axial levels. Our findings offer a new perspective of how Hox genes produce global patterns in the axial skeleton and support a redundant nonmyogenic role of Myf5 and Myf6 in rib formation.